THE INFLUENCE OF CAR, LDR, BOPO AGAINST COMPANY VALUE THROUGH GROWTH OF ASSETS IN CONVENTIONAL BANKS LISTED IN INDONESIA STOCK EXCHANGE PERIOD 2013-2017 - Muhammad Asli; Syamsu Alam; Erlina Pakki (Hasanuddin Journal of Applied Business and Entrepreneurship, 2020)
The banking sector plays an important role in a country's economy, because banks are intermediary institutions connecting between people who have excess funds and people who need funds. This study aims to determine the effect of CAR, LDR, BOPO on Company Value through Asset Growth in Conventional Banks Listed on the Indonesia Stock Exchange for the period of 2013 to 2017. The results of the study found that CAR has a positive and real influence in increasing asset growth , LDR has positive and significant effect in increasing asset growth, BOPO has a negative and significant effect on asset growth, CAR has a positive and significant effect on company value, LDR has positive and significant effect on company value, BOPO has negative and significant effect on company value, asset growth positive and significant effect on company value, asset growth is not proven to mediate the effect of CAR on company value, asset growth can mediate the effect of LDR on company value, asset growth is proven to mediate the effect of BOPO on company value.